2022
DOI: 10.3390/bios12121149
|View full text |Cite
|
Sign up to set email alerts
|

A New Glutathione-Cleavable Theranostic for Photodynamic Therapy Based on Bacteriochlorin e and Styrylnaphthalimide Derivatives

Abstract: Herein, we report a new conjugate BChl–S–S–NI based on the second-generation photosensitizer bacteriochlorin e6 (BChl) and a 4-styrylnaphthalimide fluorophore (NI), which is cleaved into individual functional fragments in the intracellular medium. The chromophores in the conjugate were cross-linked by click chemistry via a bis(azidoethyl)disulfide bridge which is reductively cleaved by the intracellular enzyme glutathione (GSH). A photophysical investigation of the conjugate in solution by using optical spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In addition, the fluorescence properties of the fluorophore unit enhance the use of these molecules for theranostics. Other similar studies based on naphtalimide-bearing bacteriochlorins are also reported in recent original articles [ 202 , 204 , 205 ].…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...supporting
confidence: 61%
See 1 more Smart Citation
“…In addition, the fluorescence properties of the fluorophore unit enhance the use of these molecules for theranostics. Other similar studies based on naphtalimide-bearing bacteriochlorins are also reported in recent original articles [ 202 , 204 , 205 ].…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...supporting
confidence: 61%
“…While naturally occurring metal complexes derived from bacteriochlorophylls are unstable and have limited use, there are now synthetic compounds recently described that belong to the bacteriochlorin family and are highly photostable [ 199 , 200 ]. Therefore, two significant issues with bacteriochlorophylls must be addressed for their phototherapeutic application: firstly, they are prone to instability, which can lead to unintended dehydrogenation and subsequently the formation of a chlorin; and secondly, the rigidity of their macrocycle makes it challenging to perform synthetic transformations [ 198 , 201 , 202 ].…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
“…36 The challenge was to develop a photo-responsive triazene linker stable enough to withstand spontaneous hydrolysis during synthesis or imaging and function independently in the presence of reducing agents, in contrast to recently reported reductively cleavable photosensitized linkers. 37 We explored the synthesis of multiple triazene analogues and optimized triazene linker 3. Once installed, the linker allowed for further chemical modifications to attach handles for conjugating macromolecules to the fluorochromes.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Thus, the detection of glutathione has become a critical issue. Prof. Pavlova fabricated a new GSH probe, BChl-S-S-NI, based on the second-generation photosensitizer bacteriochlorin e6 (BChl) and a 4-styrylnaphthalimide fluorophore (NI) [1]. They verified that the energy transfer process of BChl-S-S-NI is realized with high efficiency in the conjugated system, leading to the emissions of the fluorophore fragment being quenched.…”
mentioning
confidence: 95%
“…Biocompatibility is the top priority when fluorescent materials are used in bio-fields; a great number of biocompatible fluorescent materials (BFMs) have been obtained, such as organic small-molecule dyes, fluorescent conjugated polymers, metal nanoclusters, rare earth ion-based nanoparticles (e.g., rare-earth-doped upconversion nanoparticles), quantum dots, carbon nanomaterials (e.g., carbon nanotubes and carbon nanodots) and various fluorescent proteins. This Special Issue, "Fluorescent Materials with Excellent Biocompatibility and Their Application in Bio-Sensing, Bio-Imaging", includes twelve research articles covering biosensors based on ion sensors, the detection of pathological oxidative stress and disease detection [1][2][3][4][5][6][7][8][9][10][11][12], as well as four review articles focused on different types of fluorescent probes and biological applications [13][14][15][16].…”
mentioning
confidence: 99%